2020
DOI: 10.1177/1059712320963974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and task difficulty on postural sway, variability and complexity

Abstract: This study aimed to examine the effects of age and the task difficulty on postural sway, variability and complexity. The participants were 90 able-bodied individuals including children ( n = 39; age: 5.89 ± 0.94 years), young adults ( n = 30; age: 23.23 ± 1.61 years) and older adults ( n = 21; age: 64.59 ± 5.24 years) who took part in different balance tasks that had different levels of cognitive and physical challenges. The main dependent variables were postural sway area, postural variability and postural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…gaze) complexity. Since ageing results in lower automaticity of postural sway [1][2][3]57] it is likely a greater cortical contribution is required to maintain balance in older adults [1,54,57]. This is in turn reflected in the greater coupling between sensory input and motor output, in agreement with studies demonstrating high reliance on visual information for postural control in older adults [58].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…gaze) complexity. Since ageing results in lower automaticity of postural sway [1][2][3]57] it is likely a greater cortical contribution is required to maintain balance in older adults [1,54,57]. This is in turn reflected in the greater coupling between sensory input and motor output, in agreement with studies demonstrating high reliance on visual information for postural control in older adults [58].…”
Section: Discussionsupporting
confidence: 69%
“…As in previous studies, AP sway complexity increased in dual task conditions, indicative of increased postural control automaticity with increased cognitive demand [1][2][3]. However, the results of this study indicated no change in ML or VT sway complexity .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We suggest that future studies compare different data collection times to provide an adequate record length for entropy analysis. The motor system uses different strategies for postural stability [ 60 ]. Thus, we also recommend studies that use the same methodology and analyze postural control using other nonlinear measures to better understand the postural control’s behavior or adaptive capacity during the dual-task performance.…”
Section: Discussionmentioning
confidence: 99%
“…These contrasting findings may be explained by the difference in sample populations. It has been demonstrated that postural control dynamics differ between children and adults (Bisi & Stagni, 2016 ; Shafizadeh et al, 2021 ), with children using more active, less automatic postural control mechanisms than young adults (Shafizadeh et al, 2021 ). The current population of young adults likely had sufficiently robust postural control systems to allow for a decrease in stability, as a result of less active control of posture, without risking a loss of balance.…”
Section: Discussionmentioning
confidence: 99%